Project management absolute beginner's guide - Horine, Greg (Absolute beginner's guide (Indianapolis, Ind.), 2022)
Succeed as a project manager, even if you've never run a project before! This book is the fastest way to master every project management task, from upfront budgeting and scheduling through execution, managing teams through closing projects, and learning from experience. Updated with more insights from the front lines, including agile approaches, dealing with security and privacy priorities, and leading remote/virtual teams, along with the latest on Microsoft Project and PMI standards and certifications and a special bonus chapter on preparing for the new PMP certification. This book will show you exactly how to get the job done, one incredibly clear and easy step at a time. Project management has never, ever been this simple! This is today's best beginner's guide to modern project management--simple, practical instructions for succeeding with every task you'll need to perform! * Master the key skills and qualities every project manager needs * Learn how to lead projects, not just "manage" them * Avoid 15 most common mistakes new project managers make * Learn from troubled, successful, and "recovered" projects * Apply agile, hybrid, and traditional project management approaches * Learn the differences between a project manager, Scrum master, and product owner * Learn how DevOps and DevSecOps impact the project manager * Set the stage for success by effectively defining your project * Build a usable project plan and an accurate work breakdown structure (WBS) * Create budgets and schedules that help you manage risk * Use powerful control and reporting techniques, including earned value management * Smoothly manage project changes, issues, risks, deliverables, and quality * Manage project communications and stakeholder expectations * Organize and lead high-performance project teams * Manage cross-functional, cross-cultural, and virtual projects * Get started with agile and "critical chain" project management * Gain key insights that will accelerate your learning curve * Learn how to respond to real-life situations, not just what they teach you in school.